Conventions of Radka Denemarková’s Novel Peníze od Hitlera (Money from Hitler) along with its Reception - Holý, Jiří (Poznańskie Studia Slawistyczne, 2017)
Radka Denemarková’s Peníze od Hitlera (Money from Hitler), edited in 2006, is a succesful novel. It has been perceived by critics as a significant work and traslated into ten languages. Despite this positive response, it is my belief that the novel is not an outstanding work. The construction of the text is full of stereotypes. It uses well-worn narrative procedures, conventional images and symbols as well as banal metaphors. That is why the credibility of the characters and situations presented in Peníze od Hitlera disappears very often. There is also a preexisting model of this novel, the play Der Besuch der alten Dame (1956, The Visit of the Old Lady), written by Friedrich Dürrenmatt. Unlike Dürrenmat, Denemarková emphasizes the dark scenes and the melodramatic emotionality of her novel. Therefore, her work is close to conventional clichés.